Tlatelolco platform on environment and development (UN.ECLAC Port of SpainTT, 1992)
In adopting this Platform Latin America and Caribbean countries agreed on principles and initiatives to help ensure the sustainability and equity of development processes in the region. They also identified certain critical areas in which the region should redouble its efforts such as finance, technology transfer, protection of natural resources and eradication of poverty.
DC